Credit card usage among undergraduate students : a qualitative study - Muhammad Haikal Afiq Abd. Malek, 1995- , author 611989; Mohd. Effendi Yusof 638328; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018